Pengaruh Kualitas Produk Dan Citra Merek Terhadap Minat Beli Ulang Konsumen Generasi Z Pada Produk Handbody Vaseline Di Kota Bandung - Erpurini, Wala; Nuha, Fadia Fikriatun (Gorontalo Management Research, 2025)
This study aims to analyze the influence of product quality and brand image on the repurchase intention of Generation Z consumers for Vaseline Handbody products in Bandung City, both partially and simultaneously. The research employs a quantitative approach with a descriptive method, involving 120 Generation Z respondents aged 13–27 years who have purchased or used Vaseline Handbody products. The sampling technique used is purposive sampling, with the criterion that respondents must reside in Bandung City. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 30. The findings reveal that product quality has a positive and significant effect on repurchase intention. Brand image also has a positive and significant effect on repurchase intention, and both product quality and brand image simultaneously have a positive and significant effect on repurchase intention. These results emphasize that improving product quality, particularly in terms of fragrance longevity, and strengthening the brand image as a high-quality product can encourage Generation Z consumers to make repeat purchases.